Cross-Ocean Distribution of Rhodobacterales Bacteria as Primary Surface Colonizers in Temperate Coastal Marine Waters - Dang, Hongyue (American Society for Microbiology (ASM), 2008)
Bacterial surface colonization is a universal adaptation strategy in aquatic environments. However, neither the identities of early colonizers nor the temporal changes in surface assemblages are well understood. To determine the identities of the most common bacterial primary colonizers and to assess the succession process, if any, of the bacterial assemblages during early stages of surface colonization in coastal water of the West Pacific Ocean, nonnutritive inert materials (glass, Plexiglas, and polyvinyl chloride) were employed as test surfaces and incubated in seawater off the Qingdao coast in the spring of 2005 for 24 and 72 h. Phylogenetic analysis of the 16S rRNA gene sequences amplified from the recovered surface-colonizing microbiota indicated that diverse bacteria colonized the submerged surfaces. Multivariate statistical cluster analyses indicated that the succession of early surface-colonizing bacterial assemblages followed sequential steps on all types of test surfaces. The Rhodobacterales, especially the marine Roseobacter clade members, formed the most common and dominant primary surface-colonizing bacterial group. Our current data, along with previous studies of the Atlantic coast, indicate that the Rhodobacterales bacteria are the dominant and ubiquitous primary surface colonizers in temperate coastal waters of the world and that microbial surface colonization follows a succession sequence. A conceptual model is proposed based on these findings, which may have important implications for understanding the structure, dynamics, and function of marine biofilms and for developing strategies to harness or control surface-associated microbial communities.